Politik Hukum Pidana Terhadap Perbuatan Narapidana Melarikan Diri Dari Lembaga Pemasyarakatan Di Indonesia - Akbar, Muhammad Fatahillah (UI Scholars Hub, 2020)
Prison escape has been committed by many prisoners in several correctional institutions in Indonesia. Since it is not a crime under Indonesian Law, the punishment of the action is merely an discipline sanction. Then, the existing punishment is not sufficient to prevent and eradicate prison escape. Hence, the rehabilitation by the correctional system will never work. This paper aims to analyse how the existing legislation regulates on the prison escape and how the viable regulation in prison escape. It is proven than in the Act on Correctional Institution and in the other relevan regulations, prison escape can never be investigated since it is not a crime. Then, discipline sanction is the only punishment. In few cases, it may also be considered as durress. Furthermore, it is stated that the criminalization of prison escape is a must. It fulfils the parameters of criminalization. Hence, the prisone escape shall be considered a crime in the future law.